Respuesta :

Answer:

-4, -2, 6, 10, 12

Step-by-step explanation:

The function is h(x) = 2x + 4. H(x) is basically just another way of writing "y", so we technically have y = 2x + 4. We can complete the table by substituting the value of x that the table gives us.

The table gives us x = -4 and wants us to find h(x), or y. So, we do y = 2(-4) + 4 and we get y = -4.

The table gives us x = -3 so we do y = 2(-3) + 4 and we get y = -2.

The table gives us x = 1 so we do y = 2(1) + 4 and we get y = 6.

The table gives us x = 3 so we do y = 2(3) + 4 and we get y = 10.

The table gives us x = 4 so we do y = 2(4) + 4 and we get y = 12.